The mosques of Egypt - O'Kane, Bernard (American University In Cairo Press, 2016)
Less than ten years after the death of the Prophet Muhammad, the new religion of Islam arrived in Egypt with the army of Amr ibn al-As in AD 639. Amr immediately established his capital at al-Fustat, just south of modern Cairo, and there he built Africa's first mosque, one still in regular use today. Since then, governors, caliphs, sultans, amirs, beys, pashas, among others, have built mosques, madrasas, and mausoleums throughout Egypt in a changing sequence of Fatimid, Ayyubid, Mamluk, Ottoman, and modern styles. Here, a leading historian of Islamic art and culture celebrates the great variety of Egypt's mosques and related religious buildings, from the early congregational mosques, through the medieval mausoleum--madrasas, to the neighborhood mosques of the Ottoman and modern periods. With outstanding architectural photography and authoritative descriptive texts, this book will be valued as the finest on the subject by scholars and general readers alike. Includes more that 80 of the country's most historic mosques, with more than 500 color photographs. -- Inside jacket flap